MUSYKIL HADIS TENTANG ANJURAN AMAR MAKRUF DAN NAHI MUNGKAR - Rachmat bin Badani Tempo (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2023)
This study aims to determine the content of Anas bin Malik's hadith regarding the advice to amar makruf and nahi munkar which contradicts other Shari'a arguments from the Al-Qur'an and the hadiths of the Prophet. This research is a descriptive research with library research method or document study and normative and historical approaches. Through this research, several results were found: first, Anas bin Malik's hadith is a very weak hadith because it was narrated through weak narrators, and there is no other route from mutabi' that can strengthen it. Likewise, the hadith of Abu Hurairah, whose status is a martyr, was also punished weakly because the masdar hadith of Ṭalhah bin 'Amr had been abandoned by hadith scholars. Therefore, these two hadiths cannot mutually reinforce one another. Second, this sabāb al-wurūd hadith of Anas is a friend's question to Rasulullah saw. are we not allowed to call mankind to goodness until we do it first, and we are not forbidding mankind from evil until we leave it first. Third, this hadith contains a call to order mankind to do good and forbid them from evil. Although the hadith of Anas bin Malik ra. this is very weak, as is the case with the hadith of Abu Hurairah ra, but the meaning of this hadith is correct and does not contradict other arguments from both the Koran and the hadiths of the Prophet. It can even be said that the meaning of Anas' hadith is a bayan or explanation of the generality of the verses and hadiths of the Prophet. another.